Impact of work from home on employee wellbeing during pandemic - MONICA, DR. BENITA. S.; MS. GHAYATHRI N (The journal of contemporary issues in business and government, 2020)
The research paper title work from home: A study on wellbeing of employees during work from home during coronavirus pandemic. The main objective of the study is to know how the employee wellbeing is affected due to work from home. Especially in the IT industry the work life balance of the employees is affected badly. The descriptive research is used in this study as the research design and the sampling method is used as the convenience sampling. The size of the sample collected in this study is sixty (60) also the primary data is used. The statistical tools used in this study are frequency analysis, mean analysis and regression. Regression analysis is used to measure the wellbeing of the employees during COVID-19 pandemic. The components used to measure the impacts of work from home on employee wellbeing are work demands, home demands, work interfering with family, family interfering work and employee wellbeing. This analysis will be useful for the human resource managers to know the wellbeing of the employees during work from home.